Antibacterial activity of the oregano extract Origanum vulgare emulsioned on bovine mastitis - Bravo Loor, Johnny (2019)
Aqueous extract of oregano leaves Origanum vulgare was obtained to determine its antibacterial activity in cows in production with bovine mastitis distilled by steam entrainment, with 12 and 14% concentration in phenolic compounds and it was emulsified (O/W) using two methods: ultrasound and magnetic stirring. For the diagnosis, the California test (CMT) was used and confirmed by somatic cell count (SCC) by fixed cytometry and colony- forming units (CFU) / mL in Mannitol and MacConkey agar crops for Staphyloccocus aureus and Escherichia coli respectively. The application of 5 mL of the emulsified extract via intramammary after milking and breastfeeding for 3 days with stainless steel cannulas. The trial was conducted in a completely randomized design and analysis of variance with bifactorial arrangement; The results indicate non-significant statistical differences for the CCS and CFU / mL between the concentrations (12 and 14%) of phenolic compounds. However, there actually were significant differences p <0.05 for the method of ultrasound processing in the CFU / mL for colonies of S. aureus and the CCS, so it is concluded that the product has an inhibitory effect on this bacterium.